The Role of Certified Electronic Signatures in Ensuring the Legal Certainty of Digital Contracts Following Amendments to the ITE Law - Hani Rosdiana; Citraresmi Widoretno Putri (NOTARIIL Jurnal Kenotariatan, 2026)
Digital transformation has shifted conventional contracting practices toward electronic contracts, raising issues of legal certainty, particularly regarding identity verification and the validity of legal obligations. Although Indonesian law has recognized electronic documents as evidence, there remains a gap between classical civil law norms and digital evidence practices, especially following the 2024 amendment to the ITE Law, which has not yet been extensively examined from a technical-legal perspective. This study aims to analyze the transformation of the subjective requirements of a contract (consent and capacity) through digital identity mechanisms, evaluate the degree of legal certainty between certified and uncertified Electronic Signatures, and formulate a regulatory harmonization model between contract law and the operational standards of Electronic Certification Providers. The method used is normative legal research with a legislative and conceptual approach through a literature review. The results of the study indicate that certified electronic signatures are capable of strengthening the proof of agreement and verifying the identities of the parties more objectively through mechanisms of authentication, integrity, non-repudiation, and time validity, thereby increasing the degree of legal certainty compared to uncertified electronic signatures. However, this strength is not absolute as it remains dependent on the reliability of the system and does not replace substantive legal assessment of the parties’ capacity and free will. This study also produced an integrative and preventive regulatory harmonization model by positioning electronic certification as part of the validation mechanism in the formation of legal obligations. These findings contribute to the development of digital contract law by positioning certified electronic signatures as a crucial instrument in strengthening the evidence of compliance with the legal requirements of agreements in the digital era.